Fundamentals of design of jet-drop optical systems for three-coordinate measurements of electric, magnetic and gravitational field strengths by the pendant drop method. Part 1 - E. V. Leun (Омский научный вестник, 2023)
The article discusses the principle of operation and the main components of jet-drop optical measuring systems (JDOMS) based on the pendant drop method for monitoring electric field strength (EFS), magnetic field (MFS) and gravitational field (GFS). To make a pendant drop sensitive to electric or magnetic fields, it is proposed to charge it electrostatically or to create it from a magnetic fluid, and its mass allows you to feel changes in the gravitational field. The use of magnetic fluids as the basis of a pendant drop is the most multifunctional for measurements of EFS, MFS and GFS. The implementation of the zero measurement method using a pendant drop as a comparison device, a null organ that perceives the difference in the effects of the measured and reference field(s) at the level of quasi-zero three-coordinate displacements, is considered. They are measured by high-precision optical measurement methods. Different variants of modern optical measurement systems are analyzed.